Priming exercise accelerates oxygen uptake kinetics during high-intensity cycle exercise in middle-aged individuals with type 2 diabetes - Egana, Mikel (My University, 2022)
Background: The primary phase time constant of pulmonary oxygen uptake kinetics ( ⋅VO2 τ p) during submaximal efforts is longer in middle-aged people with type 2 diabetes (T2D), partly due to limitations in oxygen supply to active muscles. This study examined if a high-intensity "priming" exercise (PE) would speed ⋅VO2 τ p during a subsequent high-intensity cycling exercise in T2D due to enhanced oxygen delivery. Methods: Eleven (4 women) middle-aged individuals with type 2 diabetes and 11 (4 women) non-diabetic controls completed four separate cycling bouts each starting at an 'unloaded' baseline of 10 W and transitioning to a high-intensity constant-load. Two of the four cycling bouts were preceded by priming exercise. The dynamics of pulmonary ⋅VO2 and muscle deoxygenation (i.e. deoxygenated haemoglobin and myoglobin concentration [HHb + Mb]), were calculated from breath-by-breath and near-infrared spectroscopy data at the vastus lateralis, respectively. Results: At baseline ⋅VO2 τ p, was slower (p < 0.001) in the type 2 diabetes group (48 ± 6 s) compared to the control group (34 ± 2 s) but priming exercise significantly reduced ⋅VO2 τ p (p < 0.001) in type 2 diabetes (32 ± 6 s) so that post priming exercise it was not different compared with controls (34 ± 3 s). Priming exercise reduced the amplitude of the ⋅VO2 slow component (As) in both groups (type 2 diabetes: 0.26 ± 0.11 to 0.16 ± 0.07 L/min; control: 0.33 ± 0.13 to 0.25 ± 0.14 L/min, p < 0.001), while [HHb + Mb] kinetics remained unchanged. Conclusion: These results suggest that in middle-aged men and women with T2D, PE speeds ⋅VO2 τ p likely by a better matching of O2 delivery to utilisation and reduces the ⋅VO2 As during a subsequent high-intensity exercise.
PUBLISHED
Keywords: Oxygen uptake slow component; Oxygen extraction; Near-infrared spectroscopy; Cycling; Exercise tolerance